Moving beyond Country Rankings in International Assessments: The Case of PISA. Issue 1 (January 2015) - Perry, Nancy; Ercikan, Kadriye
The Programme for International Student Assessment (PISA) was designed by the Organisation for Economic Cooperation and Development (OECD) to evaluate the quality, equity, and efficiency of school systems around the world. Specifically, the PISA has assessed 15-year-old students' reading, mathematics, and science literacy on a 3-year cycle, since 2000. Also, the PISA collects information about how those outcomes are related to key demographic, social, economic, and educational variables. However, the preponderance of reports involving PISA data focus on achievement variables and cross-national comparisons of achievement variables. Challenges in evaluating achievement of students from different cultural and educational settings and data concerning students' approaches to learning, motivation for learning, and opportunities for learning are rarely reported. A main goal of this themed issue of Teachers College Record (TCR) is to move the conversation about PISA data beyond achievement to also include factors that affect achievement (e.g., SES, home environment, strategy use). Also we asked authors to consider how international assessment data can be used for improving learning and education and what appropriate versus inappropriate inferences can be made from the data. In this introduction, we synthesize the six articles in this issue and themes that cut across them. Also we examine challenges associated with using data from international assessments, like the PISA, to inform education policy and practice within and across countries. We conclude with recommendations for collecting and using data from international assessments to inform research, policy, and teaching and learning.